Fermentative hydrogen and methane co-production from pretreated Spartina anglica biomass with optimal saccharification effect under acid/alkali-assisted steam/microwave heating and enzymolysis. (1st November 2016) - Ding, Lingkan; Cheng, Jun; Yue, Liangchen; Liu, Jianzhong; Zhang, Li; Zhou, Junhu; Cen, Kefa
Highlights: S. anglica was pretreated by acid/alkali-assisted steam/microwave heating (S/MH). Acid-assisted SH generated smaller and more regular fragments and debris (5–30 μm). Dilute acid increased the reducing sugar yield by 0.598 g/g-VS than alkali in SH. Acid-assisted SH with enzymolysis exhibited a saccharification efficiency of 98.96%. Energy conversion efficiency of S. anglica was 74.9% in H2  + CH4 production. Abstract: The exotic species Spartina anglica spread in coastal beaches of China was first used as a potential biomass resource to co-produce hydrogen and methane through dark fermentation. S. anglica was subjected to four pretreatments, including alkali-assisted microwave heating (MH), alkali-assisted steam heating (SH), acid-assisted MH, and acid-assisted SH. Scanning electron micrographs revealed that acid-assisted SH disrupted S. anglica more thoroughly, resulting in the generation of smaller fragments and debris (5–30 μm). The acid-assisted SH pretreated S. anglica biomass with enzymolysis exhibited the highest reducing sugar yield of 0.743 g/g-volatile solids (VS), corresponding to a saccharification efficiency of 98.96%. The fermentative hydrogen yield from pretreated S. anglica was 135.9 mL/g-VS and the acetate and butyrate comprised 92.5% of the soluble metabolic products. Subsequent methane yield from the hydrogenogenic effluent reached up to 268.5 mL/g-VS. The energy conversion efficiency of S. anglica dramatically increased from 9.9% in fermentative hydrogen production to 74.9% in fermentative hydrogen and methane co-production.